2003
DOI: 10.1006/viro.2002.1777
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Vpr Activates Cell Cycle Inhibitor p21/Waf1/Cip1: A Potential Mechanism of G2/M Cell Cycle Arrest

Abstract: The Vpr gene of human immunodeficiency virus type 1 (HIV-1) encodes a 14-kDa protein that prevents cell proliferation by causing arrest in the G2/M phase of the cell cycle. Here we report the first evidence that Vpr activates the expression and transcription of the cyclin-dependent kinase inhibitor p21/Waf1/Cip1 (hereafter p21), an inhibitor of the G1 and G2/M phase transitions in T lymphoid and myeloid cells. Vpr activated p21 protein expression in a dose-dependent manner. Vpr also caused a three- to eightfol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 42 publications
3
44
0
Order By: Relevance
“…Waf1 may mediate Vpr-induced G 2 arrest, although this hypothesis was not tested (12). Here we report that p21 Waf1Ϫ/Ϫ mouse embryonic fibroblasts are able to activate the G 2 checkpoint when transfected with Vpr (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Waf1 may mediate Vpr-induced G 2 arrest, although this hypothesis was not tested (12). Here we report that p21 Waf1Ϫ/Ϫ mouse embryonic fibroblasts are able to activate the G 2 checkpoint when transfected with Vpr (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…The cyclin-dependent kinase inhibitor p21 Waf1 was previously shown to be transcriptionally upregulated in a p53-dependent fashion in the context of Vpr expression (12). This observation led the authors to formulate the hypothesis that p21…”
Section: Discussionmentioning
confidence: 99%
“…Human papillomavirus type 1 (HPV1), reoviruses, and SV40 also prevent activation of CDK1 by maintaining the inhibitory phosphorylation of CDK1 (35)(36)(37). HIV VPR alternatively upregulates the CDK inhibitor p21, which helps to maintain the inactive state of the cyclin B1/CDK1 complex (38). The agnoprotein of JC polyomavirus also induces p21 to inhibit the activation of the cyclin B1/CDK1 complex (39).…”
Section: Discussionmentioning
confidence: 99%
“…Vpr expression in various cell types leads to G2 cell cycle arrest. It does so through increased expression of p21 through the p53 pathway, a major regulator of progression through the G2 and M phases (Chowdhury et al, 2003). Vpr seems to act synergistically with p53, perhaps inducing transcription of p21 through its own transactivation mechanisms.…”
Section: G2 Cell Cycle Arrestmentioning
confidence: 96%
“…At least two studies indicated that mutagenesis of A30 to leucine also abolished cell cycle arrest and reduced the transcription of p21 (Chowdhury et al, 2003;Mahalingam et al, 1997). As noted above, A30L eliminated oligomerization, which suggests a correlation between the functions of oligomerization and G2 cell cycle arrest.…”
Section: G2 Cell Cycle Arrestmentioning
confidence: 99%